NATIONAL SECURITY RESEARCH IN THE AGE OF BIG DATA (Scientific journal of the Fergana State University, 2023)
Over the past decade, «big data» has become a ubiquitous buzzword in academia, the professional world, and the media. Some commentators have called big data «the new oil of the 21st century» and «the most valuable resource in the world». As technology advances and data becomes available, computing power increases, just as Moore's law predicted in the 1970s. The rapid development of tools and sensors, digital storage and computing, communications and networks has led to an inevitable “big data revolution” that generates and makes more and more data available. It has enormous implications for national governance, political and militaries, national security, corporate decisions, and individual lifestyles. In the face of the growing flow of big data, existing national security management practices can no longer meet the security requirements of the big data era, and national security is facing serious challenges.